Pleural and mediastinal effusions after the extracardiac total cavopulmonary connection: Risk factors and impact on outcome - Heinisch, Paul Philipp; Metz, Paul; Staehler, Helena; Mayr, Benedikt; Vodiskar, Janez; Strbad, Martina; Ruf, Bettina; Ewert, Peter; Hager, Alfred; Hörer, Jürgen; Ono, Masamichi (Frontiers in Cardiovascular Medicine, 2022)
Background: This study investigated the volume and duration of pleural and mediastinal effusions following extracardiac total cavopulmonary connection, as well as preoperative risk factors and their impact on outcome. Methods: A total of 210 patients who underwent extracardiac total cavopulmonary connection at our center between 2012 and 2020 was included in this study. Postoperative daily amount of pleural and mediastinal drainage were collected and factors influencing duration and amount of effusions were analyzed. The impact of effusions on adverse events was analyzed. Results: Median age at extracardiac total cavopulmonary connection was 2.2 (interquartile range, 1.8-2.7) years with median weight of 11.6 (10.7-13.0) kg. Overall duration of drainage after extracardiac total cavopulmonary connection was 9 (6-17) days. The total volume of mediastinal, right pleural, and left pleural drainage was 18.8 (11.9-36.7) ml/kg, 64.4 (27.4-125.9) ml/kg, and 13.6 (0.0-53.5) ml/kg, respectively. Hypoplastic left heart syndrome (p=0.004) and end-diastolic pressure (p=0.044) were associated with high volume of drainages, and hypoplastic left heart syndrome (p=0.007), presence of aortopulmonary collaterals (p=0.002), and high end-diastolic pressure (p=0.023) were associated with long duration of drainages. Dextrocardia was associated with higher volume (p<0.001) and longer duration (p=0.006) of left pleural drainage. Duration of drainage was associated with adverse events following extracardiac total cavopulmonary connection (p=0.015). Conclusions: Volume and duration of pleural and mediastinal effusions following extracardiac total cavopulmonary connection were related with hypoplastic left heart syndrome, aortopulmonary collaterals, and end-diastolic pressure. The duration of drainage for effusions was a risk factor for adverse events after total cavopulmonary connection.